Utilization Of Setaria Sphacelata Variety Splendida By Kedah-Kelantan Cattle - Sidik Budiono, Romziah (1985)
There is limited information on Deer production from pasture in Malaysia, particularly on optimization of land for maximum production. Setaria sphacelata variety splendida is a tropical grass species which has been successfully established in Malaysia as a fodder for cattle. However, optimum stocking rates and grazing systems for Setaria sphacelata variety splendida pasture for maximum productivity for beef cattle has not been established. The objective of this study was to determine the average daily gain per animal and total gain per hectare for Kedah- Kelantan cattle, the indigenous beef cattle in Malaysia. For this purpose experiments were conducted to determine the dry matter yield, chemical composition and digestibility using the nylon bag technique (Experiment I) and in vivo digestibility o f a Setaria sphacelata variety splendida pasture (Experiment II). Later experiment s examined the effects of stocking rate, grazing system and urea-mollases supplementation (Experiment III) and energy and/or mineral supplementation (Experiment IV) on daily gain and total gain/ha of Kedah-Ke lantan bull s grazed o n a Setaria sphacelata variety splendida pasture .